2005
DOI: 10.1159/000089269
|View full text |Cite
|
Sign up to set email alerts
|

Serum Paraoxonase 1 Activity and Lipid Peroxidation Levels in Patients with Age-Related Macular Degeneration

Abstract: Our objective was to investigate antioxidant paraoxonase 1 (PON1) activity together with malondialdehyde (MDA) levels to evaluate oxidative stress in patients with age-related macular degeneration (AMD), an important cause of blindness in the elderly population. Serum PON1 activity and MDA levels were analyzed in 37 patients with AMD and compared with 29 healthy controls using a spectrophotometric method. Serum MDA levels were significantly higher in the patient group (2.76 ± 1.28 nmol/ml) than controls (1.00 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…In the study by Baskol et al (2006), PON1 activity was lower in the patients with nonexudative-type AMD than in the controls. In another study, Ikeda et al (2001) reported that the paraoxonase gene polymorphisms might be a possible genetic risk factor for exudative-type AMD.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the study by Baskol et al (2006), PON1 activity was lower in the patients with nonexudative-type AMD than in the controls. In another study, Ikeda et al (2001) reported that the paraoxonase gene polymorphisms might be a possible genetic risk factor for exudative-type AMD.…”
Section: Discussionmentioning
confidence: 70%
“…PON1 has been shown to neutralize the harmful effects of lipid peroxides by diminishing covalent linkages between lipid peroxidation products and LDL protein, as well as the accumulating lipid peroxides in LDL (Harangi et al 2008). Baskol et al (2006) concluded that the increased ROS levels might cause increased lipid peroxidation, and thus, result in decreased antioxidant PON1 activity and increased MDA levels. They also determined a significant negative correlation between MDA and PON1 activities in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…PON1 catalyzes the breakdown of organophosphates (Jakubowski, 2000;Josse et al, 2001) and also hydrolyzes homocysteine thio-lactone, which can harm some proteins by homocysteinylation. Reduced PON1 activities have been reported in cardiovascular diseases (McElveen et al, 1986;Navab et al, 1997), diabetes mellitus (Abbott et al, 1995;Mackness et al, 1998;Sakai et al, 1998), chronic renal failure (Dantoine et al, 1998), rheumatoid arthritis (Baskol et al, 2005), hyperthyroidism (Raiszadeh et al, 2004), age-related macular degeneration (Baskol et al, 2006) and in cataract (Hashim and Zarina, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a strong correlation between PON1 levels and TBARS seems to be associated with the pathology of CRVO. Baskol et al 15 observed an increase in MDA levels related to decreased PON1 activity in patients with age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 98%
“…14 The PON1 enzyme, which has been implicated in the pathogenesis of atherosclerosis, has not been studied in the context of RVO diseases, although a decreased PON1 activity correlating negatively with malondialdehyde (MDA) levels that evaluates oxidative stress has been reported in patients with age-related macular degeneration. 15 Serum PON1 is also one of the endogenous free-radical scavenging systems in the human body. Serum PON1, together with ARE, has been demonstrated to function as a single enzyme.…”
Section: Introductionmentioning
confidence: 99%